2012
DOI: 10.4034/pboci.2012.122.19
|View full text |Cite
|
Sign up to set email alerts
|

Manifestações Orais e Maxilofaciais Secundárias à Bulimia Nervosa: Uma Revisão Sistemática

Abstract: Introdução: A bulimia nervosa é um tipo de transtorno alimentar (fortemente associado à questão do padrão de beleza corporal contemporâneo) que atinge cerca de 1 a 2% da população, com maior prevalência no gênero feminino, apresentando uma gama de alterações importantes e características que acometem a região oral e maxilofacial. Objetivo: Realizar uma revisão da literatura a cerca das publicações sobre as manifestações bucomaxilofaciais secundárias à bulimia nervosa, demonstrando as alterações mais comuns e a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…These inadequate eating behaviors may lead to dental problems, such as tooth sensitivity, fractures and dental loss, increased caries index and dental erosion, the latter being the most cited in the literature 9 . Dental erosion is characterized by irreversible loss of the mineral structure through a pathological and chronic process due to the chemical etch on the tooth surface by acid and/or chelation without bacterial involvement, originating from extrinsic or intrinsic factors 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These inadequate eating behaviors may lead to dental problems, such as tooth sensitivity, fractures and dental loss, increased caries index and dental erosion, the latter being the most cited in the literature 9 . Dental erosion is characterized by irreversible loss of the mineral structure through a pathological and chronic process due to the chemical etch on the tooth surface by acid and/or chelation without bacterial involvement, originating from extrinsic or intrinsic factors 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Medeiros et al 24 showed that not all bulimics present dental erosion and that the factors associated with the occurrence and severity of the condition are the duration of the disease, frequency of vomiting episodes, and the amount of saliva. For the diagnosis of dental erosions, a longer follow-up period is necessary as the extent of dental erosion varies over time, particularly during the development of eating disorders.…”
mentioning
confidence: 99%